2016
DOI: 10.3389/fncel.2016.00118
|View full text |Cite
|
Sign up to set email alerts
|

NSC-34 Motor Neuron-Like Cells Are Unsuitable as Experimental Model for Glutamate-Mediated Excitotoxicity

Abstract: Glutamate-induced excitotoxicity is a major contributor to motor neuron degeneration in the pathogenesis of amyotrophic lateral sclerosis (ALS). The spinal cord × Neuroblastoma hybrid cell line (NSC-34) is often used as a bona fide cellular model to investigate the physiopathological mechanisms of ALS. However, the physiological response of NSC-34 to glutamate remains insufficiently described. In this study, we evaluated the relevance of differentiated NSC-34 (NSC-34D) as an in vitro model for glutamate excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 67 publications
6
38
1
Order By: Relevance
“…In contrast, both cortical and iPS-derived sMNs displayed a more robust increase in DPR levels in the presence of the excitotoxic stressors, glutamate and homocysteine (HC), compared to NSC34 NES-mIFP cells which demonstrated insignificant densitometric DPR levels and less significant fluorescent DPR levels in the presence of glutamate. This observation may be consistent with evidence showing that NSC34 cells have decreased calcium permeability responsiveness to excitotoxic stress even when differentiated into neuronal-like cells (Madji Hounoum et al, 2016). Taken together, these results demonstrate that a spectrum of compounds, which activate a number of cellular stress pathways, all increase non-AUG-dependent translation with neurons showing heightened sensitivity to excitotoxic stressors.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, both cortical and iPS-derived sMNs displayed a more robust increase in DPR levels in the presence of the excitotoxic stressors, glutamate and homocysteine (HC), compared to NSC34 NES-mIFP cells which demonstrated insignificant densitometric DPR levels and less significant fluorescent DPR levels in the presence of glutamate. This observation may be consistent with evidence showing that NSC34 cells have decreased calcium permeability responsiveness to excitotoxic stress even when differentiated into neuronal-like cells (Madji Hounoum et al, 2016). Taken together, these results demonstrate that a spectrum of compounds, which activate a number of cellular stress pathways, all increase non-AUG-dependent translation with neurons showing heightened sensitivity to excitotoxic stressors.…”
Section: Resultssupporting
confidence: 89%
“…5). Previous studies have confirmed that 6 h of menadione administration in a redox cycling system is sufficient to increase ROS within numerous subcellular chambers [20]. In this study, PLS3 overexpression in serum-deprived NSC-34 cells promoted cell survivability following menadione administration; however, the increase in viability was not significantly different when compared to serum-deprived NT cells.…”
Section: Cell Metabolic Activity Assaycontrasting
confidence: 37%
“…Reduced, whole-well mitochondrial function could be attributable to multiple system variables: (1) reduced number of cells as a function of reduced cellular proliferation or cell death, or (2) reduced mitochondrial metabolic function of each cell, or (3) a combination of the two. The WST-1 cellular metabolic function was also inversely correlated with NSC-34 degree of neuronal differentiation, using a standard differentiation protocol widely used to produce a range of physiological and morphological changes in NSC-34 that produce a mature neuron-like phenotype [34][35][36][37]. This was not due to a general DRP-independent decline in mitochondrial function with cell aging, as DMSO-treated controls did not change in metabolic activity significantly over the same course of differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…To examine arginine-rich DRP toxicity in relation to increased degree of neuronal differentiation, DRP-treated cells that had been differentiated for either 1, 2, 3, or 4 weeks were tested in a WST-1 assay. When allowed a longer incubation period in the neuronal differentiation protocol, a protocol widely used and well-established for inducing both physiological and morphological maturation of NSC-34 cells to a mature neuron-like phenotype [34][35][36][37], the cells became more sensitive to arginine-rich DRPs (Figure 6a,b). For example, to achieve a 25% reduction in WST-1 metabolism, cells incubated for 7 days required exposure to 1000 nM GR 15 , whereas cells incubated for 28 days only required exposure to 30 nM GR 15 .…”
Section: Nsc-34 Sensitivity To Arginine-rich Drps Increases With Neurmentioning
confidence: 99%